Individual and community factors of early sexual debut among adolescents in Indonesia: Evidence from demographic and health survey - Sulistiawan, Dedik; Arifa, Riza Fatma; Matahari, Ratu; Chakranon, Pairote (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Early sexual debut by adolescents is a major public health issue with long-term consequences for sexual and reproductive health. Research has highlighted the role of social skills, peer influence, and social norms in shaping the risk of early sexual initiation among adolescents. However, there is still insufficient evidenceto contextualize the contributing factors in socio-ecological framework, especially in the era of disruptive technologies in Indonesia.Objective: This study was to examine the individual and community-level factors associated with early sexual debut in adolescents socio-ecological framework.Methods: This cross-sectional study utilizing data from the 2017 Indonesia Demographic and Health Survey (IDHS). Individual-level factors included gender, age, work and school participation, dating experience, perceived peer pressure and access to sexual and reproductive health (SRH) information. Factors at community level include the area of residence and community internet access. Multilevel logistic regression was used, with effect sizes reported as odds ratios (OR) and 95% confidence intervals (CI).Results: Adolescents with dating experience (OR: 18.41; 95% CI: 8.14–41.62), those with friends who had an early sexual debut (OR: 6.24; 95% CI: 4.81–8.09), and those who had a good understanding of pregnancy prevention (OR: 1.73; 95% CI: 1.41–2.11) were more likely to experience early sexual debut. Protective factors included discussing SRH with teachers (OR: 0.76; 95% CI: 0.64–0.90) and first exposure to SRH education at the junior (OR: 0.60; 95% CI: 0.47–0.77) or senior high school level (OR: 0.41; 95% CI: 0.23–0.74). An analysis at Community-level has shown that adolescents in areas with high internet accessare 59% less likely to engage in early sexual debut than their counterparts.Conclusion: Individual and community-level factors, including internet access, influence adolescent early sexual debut. Reinforcing sexual and reproductive health education in formal education systems is essential, especially in areas with limited acces to internet.